AI and Human Collaboration: The Future of HR in the Fourth Industrial Revolution - Zainuddin Hamidi, Dendi; Hakiki, Ridwan; Pandiangan, Hendrik (Escalate : Economics and Business Journal, 2024)
This study investigates the interplay of Adoption of Advanced HR Technologies, Workforce Management Effectiveness, Employee Engagement and Productivity, and Employee Performance within PT Danareksa (Persero), a prominent state-owned enterprise in Indonesia's financial services sector. Using a quantitative approach and Structural Equation Modeling (SEM) with Smart PLS, data from 80 employees were analyzed to explore the direct and indirect relationships among these variables. The findings reveal significant direct effects of Adoption of Advanced HR Technologies and Workforce Management Effectiveness on Employee Engagement and Productivity, highlighting their role in enhancing employee engagement and productivity levels. Moreover, both Adoption of Advanced HR Technologies and Workforce Management Effectiveness indirectly influence Employee Performance through their impacts on Employee Engagement and Productivity. These results underscore the critical importance of strategic investments in HR technologies and effective workforce management practices in optimizing organizational performance and competitiveness. This research contributes to understanding how HR innovations and management practices can foster a conducive work environment that drives employee performance and organizational success in the financial services industry.